ANALYSIS OF DISTRIBUTION SIMULATION OF SUSPENDED SLAB AND CYLINDER SUPERKONDUCTOR USING ELEMEN METHOD - Supardi Supardi (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2006)
Investigation of creation of ordered parameter distribution on superconductor material, especially cylinder form has been conducted. Distribution of ordered parameter inside the material is obtained by applying external magnetic field parallel to the surface of the material. When the external magnetic field is reduced carefully, ordered parameter distribution will create at a certain value called He).The method applied to obtain the ordered parameter distribution isfinite element method. To make easy in computation work, be applied FEMLAB software. The software works under MATLAB running. Principles of finite element method have been covered in FEMLABThe result of the numerical simulation show in line between the beginning hypothesis of researcher and computation result. Compared with previous result, the result does not deviate significantly.